Collaborative Learning and Paragraph Writing Skills: Analyzing Effects and Engagement for EFL Students - Nugroho Nugroho (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigated the effects of integrating round-robin and collaborative writing techniques on the paragraph writing performance and engagement of English as a Foreign Language (EFL) students. Employing a quasi-experimental pretest–posttest control group Design, the study involved 160 undergraduate students enrolled in compulsory writing courses, divided into an experimental group and a control group. Over six weeks, the experimental group received instruction through a combination of round-robin drafting and collaborative writing activities, while the control group received traditional, teacher-centered writing instruction. Students’ paragraph-writing ability was measured using a rubric-based writing test, and engagement was assessed using a multidimensional questionnaire covering behavioral, cognitive, affective, and emotional engagement. Results indicated that both groups showed significant improvement in paragraph writing performance; however, the experimental group achieved substantially higher posttest scores. Effect size analysis revealed a large impact of the integrated collaborative techniques (Cohen’s d = 3.12), compared to a moderate-to-large effect in the control group (d = 2.34). Normalized gain scores further confirmed the intervention’s superior effectiveness. Engagement findings showed high levels across all dimensions among students in the experimental group. These findings suggest that integrating round-robin and collaborative writing techniques provides an effective pedagogical approach for enhancing paragraph writing performance and fostering student engagement in EFL contexts. The study highlights the value of structured peer interaction and shared authorship in writing instruction.